2018
DOI: 10.1007/s10653-018-0081-4
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of mercury (Hg) and selenium (Se) in afterbirth and their relations with various factors

Abstract: The aim of the study was to evaluate Hg and Se concentrations and Se:Hg molar ratios in the placenta, umbilical cord and fetal membranes, and to examine the relationship between the concentrations of the elements and selected factors. The study material consisted of the placenta, umbilical cord and fetal membranes obtained from 91 healthy women from northwestern and central Poland. In our study mean Hg and Se concentrations in afterbirth were ~ 0.01 mg/kg dry weight (dw) and ≤ 0.5 mg/kg dw, respectively. Corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…After complete defrosting to room temperature, samples of the placenta, fetal membranes and umbilical cords were dried to a constant mass at 105 °C. The dried samples were mineralized; more details of the analytical procedures are given by Kosik-Bogacka et al [47,48]. Determination of Ag, Ca, Cd, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Sn, Sr, V and Zn was performed by spectrophotometric atomic absorption in inductively coupled argon plasma (ICP AES), on a Perkin-Elmer Optima 2000 DV (USA).…”
Section: Methodsmentioning
confidence: 99%
“…After complete defrosting to room temperature, samples of the placenta, fetal membranes and umbilical cords were dried to a constant mass at 105 °C. The dried samples were mineralized; more details of the analytical procedures are given by Kosik-Bogacka et al [47,48]. Determination of Ag, Ca, Cd, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Sn, Sr, V and Zn was performed by spectrophotometric atomic absorption in inductively coupled argon plasma (ICP AES), on a Perkin-Elmer Optima 2000 DV (USA).…”
Section: Methodsmentioning
confidence: 99%
“…There has been increasing concern about Hg exposure in high-risk groups such as pregnant women, infants and young children. Numerous studies from various countries have assessed the Hg status in pregnant women by determining the Hg levels in blood and umbilical cord blood after birth [119][120][121]. Maternal consumption of fish has been shown to increase Hg levels in cord blood, and these levels were significantly higher than other maternal groups who did not consume fish [120].…”
Section: Blood Se and Hg Levelsmentioning
confidence: 99%
“…This is especially noteworthy in regards to the otherwise self-protecting mechanisms throughout the body and the intricacies of the DNA survival modes. Currently, two studies have emerged that measured the actual selenium and mercury levels in the placenta and umbilical cord at birth in 91 Polish cases and 54 Japanese [87,88]. In one case, they found that, on a molar ratio, the Se was in excess of mercury by ratios from 6–650 and 21-fold in the other.…”
Section: Current Insightful Researchmentioning
confidence: 99%